PENERAPAN TDBA HIDROPONIK SEBAGAI MEDIA PEMBELAJARAN STEAM UNTUK MENINGKATKAN MOTORIK HALUS ANAK 5–6 TAHUN - Ulfah Nabila; Yuwan Fijar Anugrah (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2025)
This study aims to improve the fine motor skills of children aged 5-6 years through the application of hydroponic-based Planting Program in Bale Pendidikan (TDBA) with STEAM learning approach. The background of this study is based on data that about 27% of early childhood in Indonesia experience delays in fine motor development, which can hinder their success in further education. The research method used is Class Action Research (PTK) with descriptive quantitative approach, carried out in three cycles at SPS Mawar Purwakarta. Each cycle includes stages of planning, implementation, observation, and reflection, with data collection through observation, pretest, posttest, and documentation. The results showed a significant improvement in children's fine motor skills, including the ability to pinch, grip, press, string, and eye and hand coordination. The average value of fine motor skills increased from 1.33 in cycle I, to 2.46 in Cycle II, and 3.40 in cycle III. Thus, the hydroponic TDBA program has proven to be effective, fun, and contextual in supporting children's development, especially in improving fine motor skills, as well as fostering social skills, independence, and concern for the environment.